Implementation Approach of a Dynamic Protection Scheme with Binary Key-Pair - Islam, Md. Rafiqul; Selamat, Harihodin; Md. Sap, Mohd. Noor (Malaysian Journal of Computer Science, 1998)
Describes the implementation approach of a dynamicprotection scheme with binary key-pair. The algorithm forchecking validation of access request is designed with respect to the implementation approach. Discusses the efficiency of the scheme regarding various searching problems. Brief reviews of binary key method and the binary key-pair method are given. Other implementation methods of access control system that are achieved by employing an access control matrix, have also been reviewed.